Limbah Cangkang Kerang Temberungun (Telescopium telescopium) Sebagai Adsorben Logam Berat Besi (Fe2+) - Tri Paus Hasiholan Hutapea; Ayu Paramitha; Dori Rachmawani (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2019)
The decrease in water quality is caused by the presence of pollutants in the form of organic and inorganic components. Inorganic components, including heavy metals, one of which is iron (Fe). Adsorption is one of the technologies that can be used to absorb heavy metals where the adsorbent used in this study is a shell of a shell (Telescopium telescopium) to absorb iron (Fe2+). This research aims to utilize the waste of the mussel shells (Telescopium telescopium) as an adsorbent for heavy metal iron (Fe2+). The study was divided into three stages, namely the adsorbent surface characterization, determining the optimum time and determining the adsorption capacity. All stages of the study were carried out on adsorbents that were not activated and NaOH. The results showed the largest pore size after activation was 1,398 µm, while the adsorbent before activation, the largest pore size was 844.8 nm. The surface acidity of the adsorbent before activation is 5.28 mmol / g and after activation has a value of 6.74 mmol / g. The optimum time of absorption of ferrous metal ions (Fe2+) before and after activation is 60 and 30 minutes. The adsorption capacity of the adsorbents before and after activation was 11,07899 mg / g and 459,3038 mg / g, respectively. It was concluded that the shell of a temberungun shell (Telescopium telescopium) can be used as an adsorbent for heavy metal ions (Fe2+)